(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
In Latin America, most students of different educational levels have difficulties learning mathematics. One of the strategies proposed in this situation is the adaptation of the Tuning program, in which the capacities of the Latin American student to learn mathematics are delimited. Derived from the analysis and reflection of these competences, the authors of this work presents a mathematical expression, represented as a function, to answer the question, how much reasoning ability is the minimum necessary for the student to learn mathematics? For this, the theoretical and epistemological foundations that give support to this expression are presented. The conclusions indicate the benefits of the proposal of this work in the context of the difficulties that various students present in learning mathematics.